LINGUISTIC ANALYSIS OF ARTISTIC AND PSYCHOLOGICAL IMAGERY IN ENGLISH AND UZBEK NOVELS (American Journal of Pedagogical and Educational Research, 2026)
This article provides a comparative analysis of the linguistic features of the artistic-psychological image in English and Uzbek novels. The study studies the use of language tools that express the inner experiences, mental state and psychological portrait of the characters, including metaphor, epithet, internal monologue, dialogue, figurative expression and stylistic units. The individual style of the authors in creating psychological images and national-cultural characteristics in samples of English and Uzbek literature are analyzed. The results of the study serve to deepen the understanding of the linguopoetic and psycholinguistic aspects of the literary text and are of significant scientific importance for the fields of comparative literary studies and linguistics.